A defence against the arrows of the disturbance to come: royal protection and the consolidation of monastic reform under Count Arnulf I of Flanders (918–65). - Meijns, Brigitte (Early Medieval Europe, 2018)
Monastic immunities have been much studied in recent years, but the royal protection (tuitio) that was often associated with them in the documents has been comparatively neglected. This article examines King Lothar's diplomas for Flemish monasteries in the years 962–6, texts in which royal protection played a major role. It argues that the issuing of these documents reflected a conjunctural political alliance between the king and the Flemish count Arnulf I, but also that their juridical content in general, and the bestowal of protection in particular, was valued by the recipient institutions. In this way the article makes the case for a more rounded understanding of tuitio in the tenth‐century West Frankish kingdom.